NIH funding for the pediatric surgeon-scientist: An analysis of current trends - Colton D. Wayne, MD; Zachary Dumbauld, BS; Ethan Mills, BS; Diana L. Farmer, MD; Gail E. Besner, MD (Surgery Open Science)
Background/purpose: Previous studies highlighted the success of pediatric surgeons in obtaining NIH funding. Given increasing clinical demands, we sought to analyze the current state of NIH funding for pediatric surgeon-scientists. Methods: APSA membership in August 2023 was filtered for Regular/Associate members and referenced through NIH RePORTER. Data included history of prior/active NIH funding, award type/institute, and funding pathways. Demographics collected included level of professorship, post-graduate degrees, and gender. Academic productivity was assessed by PubMed publications. In addition, a survey was distributed to Regular/Associate APSA members. Results: 1079 APSA Regular/Associate members were identified. Total (previous/current) funding: 149 (13.8 %) surgeons had previous/current NIH funding, 145 with complete funding information. There were 371 previous/current grants totaling $387,148,625. 31.7 % of funded surgeons held Chair/Chief positions, 77.9 % were male, and 84.1 % had M.D. degree only. 282 (76.0 %) grants were independent, and 42 (11.3 %) were mentored. 100 (69.0 %) funded surgeons obtained independent investigator awards, 33 (22.8 %) with and 67 (46.2 %) without prior training/mentored grants. Current funding: 52 (4.8 %) surgeons had current NIH funding, with 80 grants totaling $44,232,644. 73 (91.25 %) were independent while 7 (8.75 %) were mentored awards. Academic productivity: Assessment revealed 7197 total publications (range = 0–207, mean = 49.6). Survey: results highlighted perceived challenges and suggested improvements. Conclusions: Compared to a 2013 study by King et al., the percent of funded APSA members has trended downward; however, the number of funded pediatric surgeon-scientists and dollar amount of active NIH funds has increased. Concentrated efforts are needed to support surgical trainees and junior faculty, particularly females, to pursue research and academic pediatric surgery.